Mannosylated solid lipid nanoparticles for the selective delivery of rifampicin to macrophages - Vieira, A (2018)
Tuberculosis (TB) is still a devastating disease and more people have died of TB than any other infectious diseases throughout the history. The current therapy consists of a multidrug combination in a long-term treatment, being associated with the appearance of several adverse effects. Thus, solid lipid nanoparticles (SLNs) were developed using mannose as a lectin receptor ligand conjugate for macrophage targeting and to increase the therapeutic index of rifampicin (RIF). The developed SLNs were studied in terms of diameter, polydispersity index, zeta potential, encapsulation efficiency (EE) and loading capacity (LC). Morphology, in vitro drug release and differential scanning calorimetry studies, macrophage uptake studies, cell viability and storage stability studies were also performed. The diameter of the SLNs obtained was within the range of 160–250 nm and drug EE was above 75%. The biocompatibility of M-SLNs was verified and the internalization in macrophages was improved with the mannosylation. The overall results suggested that the developed mannosylated formulations are safe and a promising tool for TB therapy targeted for macrophages.